(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Amyotrophic lateral sclerosis (ALS) is a relentlessly progressive neurodegenerative disease characterized by dysfunction and loss of motor neurons in the brain and or spinal cord. Potential biomarkers like homocysteine (Hcy) that are sensitive to the progression of disease, which might enhance the diagnostic algorithm and provide new drug targets, are now being on trial. Several studies found elevated serum Hcy level with ALS than in normal people. Elevated Hcy is associated with duration of illness and also severity of illness. Objective: Aim of this study was to determine whether plasma Hcy levels were elevated in ALS patients than healthy control. Methods: This case control study was done with 42 patients of ALS fulfilling the inclusion and exclusion criteria and similar number of age and sex matched healthy person were taken as comparison. Result: In this study the mean age of the cases and control were 41.55±14.9 years and 42.78±14.87 years respectively. Maximum respondents were in between 30-50 years age group (Table-1). Higher frequency ofALS patients was found in male (78.6%) than female (21.4%). Among the cases majority 34(80.95%) had the onset of ALS by spinal/limb involvement and bulbar onset were 8(19.05%). Majority of patient (73.81%) had weakness of all four limbs. Study variable analysis revealed that the mean Hcy level in ALS cases was higher 14.06 mg/dl with SD 7.02 than in control 10.43 mg/dl with SD 2.85 and p value was <0.003 which explains Hcy level significantly elevated in ALS. The frequency of hyperhomocysteinemia (>15µmol/L) among case and control Group were found 33.3% versus 7.1% respectively which is statistically significant (p =<0.003). The odds ratio for hyperhomocysteinemia between case and control is 6.5(95% CI: 1.71-24.78). The Odds ratio was 6.5, indicating that the homocysteine higher than >15µmol/L increases the risk of ALS by 6.5 times. Conclusion: The present study demonstrated that HCY levels are significantly elevated in the serum of ALS patients compared to well-matched controls. Eleveted homocysteine level increases the risk of ALS. Since most of the ALS cases reveal delayed symptoms; therefore, HCY levels could be considered a biomarker of disease progression in the early phase in ALS patients.